Critical success factors of university-industry R&D collaborations - Fernandes, Aldora Gabriela Gomes (2023)
University-industry R&D collaborations (UICs) play a vital role in stimulating open innovation that leads to new products, processes, and services that creates value for customers and broader societal impact. UICs, however, commonly fail to meet these stakeholders' benefits. This study identifies thirty-four critical success factors (CSFs) for improving UIC success. The study includes a systematic literature review and a longitudinal UIC case study between Bosch Car Multimedia in Portugal and University of Minho, a multi-million Euro R&D collaboration from 2013 to 2021. The importance of the CSFs is discussed in the context of the UIC lifecycle. A survey among researchers and industry practitioners involved in R&D collaborative projects was completed to confirm the analysis of the empirical results. This paper provides UIC managers with CSFs, which, when addressed competently, can provide a basis for successful UIC projects and sustainable university-industry collaborations.